Promoting effective political socialisation strategies for youth leadership development among Universiti Putra Malaysia student leaders - Rasheed, Isau Olagoke; Ismail, Ismi Arif; Zulkifly, Nurul Afiqah (Knowledge Words Publications, 2024)
Agencies of political socialisation facilitate transmission of political orientations, attitudes, and values to young citizens in the society. Youth are valuable assets that require proper political knowledge to maintain noble ideals and socially cherished norms across generations. This paper explored the relevance of family, educational institution, peer group and media in shaping youth leadership roles in the country. In contemporary times, these agencies work together and adopt strategies such as political learning, pubic sensitization, mentoring, and youth-oriented activities to get university students accustomed to leadership process of influencing group of individuals with a view to making meaningful contributions to the society. The student leaders apply orientations so acquired to conduct purposeful leadership activities on and off-campus. Data for this study was gathered from 17 informants through semi-structured qualitative interviews. The respondents are members of the Student Representative Council of the university. Findings from the study indicated that agencies of political socialisation inculcate right values in young people, stimulate effective leadership activities, promote progressive change in the community and improve quality of youth leadership development. Further research could undertake an in-depth investigation into the efficacy of political socialization strategies on leadership activities of student leaders in public universities across Selangor, Malaysia. Based on this, the paper recommends that socializing agents be structured to properly shape youth political behaviours, create enabling environment for continuous political awareness, enhance youth involvement in leadership training programmes towards fostering experiential learning among student leaders.